Complex Earthquake Sequences On Simple Faults. Issue 17 (6th September 2019) - Cattania, C.
Abstract: While power law distributions in seismic moment and interevent times are ubiquitous in regional earthquake catalogs, the statistics of individual faults remains controversial. Continuum fault models without heterogeneity typically produce characteristic earthquakes or a narrow range of sizes, leading to the view that regional statistics originate from interaction of multiple faults. I present theoretical arguments and numerical simulations demonstrating that seismicity on homogeneous planar faults can span several orders of magnitude in rupture dimensions and interevent times, if the fault dimension W is sufficiently large compared to a characteristic length L crit, related to the nucleation dimension. Large faults are increasingly less characteristic, with the fraction of system‐size ruptures proportional to ( L crit / W ) 1/2 . Earthquake statistics for large W / L crit is remarkably close to nature, exhibiting Omori decay and power law distributed rupture lengths. Simple crack models are consistent with a Gutenberg‐Richter distribution with b =3/4 and provide a physical basis for these distributions on individual faults. Key Points: Numerical simulations and fracture mechanics predict the occurrence of partial ruptures on sufficiently large faults loaded by creep Earthquake statistics is controlled by the ratio of fault dimension to a critical length related to the nucleation dimension Large faults exhibit afterslip‐driven temporal clustering and power law distribution of seismic moments with a theoretical b value of 3/4